FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI LANSIA DALAM MENGIKUTI TERAPI AKTIVITAS KELOMPOK DI PANTI SOSIAL TRESNA WERDHA ’’ILOMATA’’ KOTA GORONTALO - Rona Febriyona; Riyan Hardichal (-, 2021)
Human elderly person is her age undurego the change of biological, physical, psychological, and social. Physical changes include the decline in physical strength, stamina, and perfomance. The aim of this research wa to know the factors that related with the elderly motivationin participating in a group activity therapy. This research was observational analytic method with cross sectional, with the  sample 35 people with a total sampling technique. The variables studied perception, environment, attitude and motivation in participating the group activity therapy  in rehabilitation center tresna werdah "Ilomata" Gorontalo city. The conclution that has a relationship between the attitudes and motivations of elderly in following TAK.